PENGARUH PEMBERDAYAAN ANGGOTA TERHADAP SIKAP MENABUNG ANGGOTA PADA CREDIT UNION MUARE PESISIR SUNGAI KAKAP - Yati, Yati; Asriati, Nuraini; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis aims to determine the influence of members empowerment on the attitude of saving members on the coastal CU Muare in District Sungai Kakap. The method used in this research is a descriptive method with the research form of relationship studies. The population in this study was 847 members and samples of 42 members. The data collection used are direct communication techniques, indirect communication, and documentary studies (member data). So researchers concluded that, 1) the empowerment of the Credit Union Muare members of the coastal district in Sungai Kakap subdistrict amounted to 74.30% belonging to the high category, 2) The attitude of saving the Credit Union Muare members of the coastal bank in the District River Kakap of 82.30% including In very high Ketagori, 3)) Thitung of 3.988 which is greater than the value of 2.201 so that it can Ha accepted and Ho rejected. The coefficient of determination (R ^ 2) indicates a figure of 0.285, thus the percentage influence of member empowerment of the member's saving attitude of 28.5%. So the conclusion contributes the influence of the empowerment of members to the attitude of saving members of CU Muare Coastal District in Sungai Kakap of 28.5%.Â Keywords: Empowerment Of Members, Attitude Of Saving, CU